2006
DOI: 10.1016/j.aim.2005.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A quantum duality principle for coisotropic subgroups and Poisson quotients

Abstract: We develop a quantum duality principle for coisotropic subgroups of a (formal) Poisson group and its dual: namely, starting from a quantum coisotropic subgroup (for a quantization of a given Poisson group) we provide functorial recipes to produce quantizations of the dual coisotropic subgroup (in the dual formal Poisson group). By the natural link between subgroups and homogeneous spaces, we argue a quantum duality principle for Poisson homogeneous spaces which are Poisson quotients, i.e. have at least one zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 16 publications
0
67
0
Order By: Relevance
“…Now, by making use of the Poisson version of the quantum duality principle [38][39][40], the group multiplication law (7) can be immediately rewritten in algebraic terms as a comultiplication map Δ z through the identification of the two copies of the dual group coordinates as…”
Section: A Dual Poisson-lie Group and Curved Momentum Spacementioning
confidence: 99%
“…Now, by making use of the Poisson version of the quantum duality principle [38][39][40], the group multiplication law (7) can be immediately rewritten in algebraic terms as a comultiplication map Δ z through the identification of the two copies of the dual group coordinates as…”
Section: A Dual Poisson-lie Group and Curved Momentum Spacementioning
confidence: 99%
“…On the other hand, the constant curvature spacetimes of 3d gravity, their isometry groups and many associated structures can be obtained from associated structures for SL(2, R) and two-dimensional hyperbolic space by analytic continuation techniques, see for instance [63,64]. Although there may be many more noncoisotropic Poisson homogeneous structures on SL(2, R)/H, it can be expected that the coisotropic ones are the simplest to quantise, see [65] and also [24][25][26][27][28][29][30][31][32][33][34][35], and most natural for applications in 3d quantum gravity and noncommutative geometry. It is therefore sensible to focus first on the coisotropic case.…”
Section: Coisotropic Poisson Homogeneous Spaces For Sl(2 R) ≃ So(2 1)mentioning
confidence: 99%
“…The Poisson homogeneous space G * /H ⊥ is called the complementary dual of G/H in [4] where it is shown that it fits into a quantum duality scheme. This map is also surjective if every g ∈ G can be written as g = kh , with h ∈ K and h ∈ H so that the last statement follows as well.…”
Section: Lemma 33 Let G Be a Poisson-lie Group H A Closed Connectementioning
confidence: 99%
“…One reason of interest lies in the fact that every coisotropic subgroup of a Poisson-Lie group can be quantized in such a way as to fit in a nice duality diagram [4]. Furthermore, coisotropic submanifolds have recently raised a lot of attention in the context of deformation quantization [3,2] and played a role in the analysis of Poisson sigma-models over group manifolds [1].…”
Section: Introductionmentioning
confidence: 99%